The challenge of wearable neurodevices for workplace monitoring: an EU legal perspective - Muhl, Ekaterina (Frontiers in Human Dynamics, 2024)
This paper explores the emerging practice of workplace surveillance by using neurotechnologies, particularly wearable neurodevices, to monitor employees' cognitive abilities, concentration levels, and emotional responses. It aims to assess the legality of such practices within the framework of EU law, focusing on the General Data Protection Regulation (GDPR) and the EU Artificial Intelligence Act (AI Act) by providing a detailed analysis of recent EU legislation in the context of the implementation of neurosurveillance at the workplace.Furthermore, the paper discusses whether current regulations adequately address the use of neurotechnologies in the workplace or are overly restrictive. It raises the question of ensuring sufficient flexibility in the regulations to allow for legitimate implementations of neurotechnologies in the labour field for workers' safety while protecting workers' rights. Overall, the paper offers insights into the intersection of neurotechnology advancements and labour relations and stimulates critical discussion about the fair balance between innovation and workers' rights.